Focused ultrasound phantom model for blood brain barrier disruption - Alekou, Tereza; Giannakou, Marinos; Damianou, Christakis A. (My University, 2021)
In this paper a high intensity focused ultrasound (FUS) phantom model was developed, in order to be used in experiments for Blood Brain Barrier (BBB) disruption. The target was to create a phantom model that represents the disruption of the BBB during ultrasound application. An appropriate experimental setup was created bearing a single element transducer with diameter 50 mm and geometric focus 100 mm operating at 0.5 MHz. It included a set of tubes and a connector with multiple 0.4 mm openings, through which a suitable liquid is being circulated with a pump. The lesions were sealed with a thin homogenous layer of wax, preventing a liquid leakage. The system was tested successfully with FUS and a liquid leakage was achieved after FUS application. This set up is the first phantom model that has the potential to be utilized as a cost-effective solution for performing experiments for BBB disruption, without the need of using animal models.
Keywords: BBB; FUS; Phantom; Ultrasound